Problems of clinical trials of cell therapy effectiveness today - A. G. Popandopulo; V. V. Turchyn; M. V. Solopov; V. V. Bushe (Сибирский научный медицинский журнал, 2021)
The main purpose of the article is to discuss the effectiveness of cell therapy. We have analyzed as example the areas trends in clinical trials to determine the effectiveness of cell therapy. The conceptual approaches to cell therapy application, results of clinical trials, identified problems have been discussed in the paper.